ANALISIS KETAHANAN PANGAN RUMAH TANGGA PETANI PADI DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Sispa Pebrian; habibah nurfaizah azra; Rosnita Rosnita; syafrinal syafrinal (Indonesian Journal of Agricultural Economics, 2022)
Food security is one of the determining factors in the country's stability in the economic, security, political and social fields. The concept of food security is not only seen through the availability of sufficient amounts of food, but also seen based on quality and balanced nutrition, food accessibility as well as food quality and safety. This study aims to determine: (1) The income and expenditure structure of rice farming households in Kuantan Singingi Regency. (2) The level of household food security of rice farmers in Kuantan Singingi Regency. The method used in this study is a survey method. Sampling used for sampling farmers is Purposive Sampling. The results of the study explain that the average total income of farming households in Singingi Regency is IDR 4,892,000/month, the average total expenditure of farming households in Singingi Regency is IDR 3,384,996/month and the food security level of rice farmers in Kuantan Regency Singingi trained based on aspects of food availability, access to food, and quality of food safety are categorized as high in increasing food security. The conclusion of this study is that the largest source of income for farming households comes from income from rice farming, and the largest source of expenditure for farming households comes from expenses for rice farming, and the level of food security for farming households in Kuantan Singingi Regency is categorized as high and households are classified as well off. to maintain and increase household food security.